“Armed in-vitro retina”-generating microglial retinal organoids, where are we now? - Liu, Yaohong; Gao, Lixiong; Chen, Wenqian; Yan, Yuhan; Ye, Zi; Li, Zhaohui (Frontiers in Cell and Developmental Biology, 2025)
The objective of organoid research is to develop in vitro models that accurately replicate the microenvironment of tissues and organs in vivo. Although techniques for culturing retinal organoids (ROs) have advanced significantly, they still fall short of incorporating all cell types necessary for maintaining retinal homeostasis, particularly immune cells like microglia. Standardizing the inclusion of immune cells in RO cultures would greatly enhance research into the mechanisms underlying retinal diseases and the discovery of therapeutic targets. This review examines recent advancements in co-culturing ROs with immune cells to mimic the physiological and pathological microenvironments of the retina, focusing on tissue structure and function. Furthermore, it emphasizes the importance of cutting-edge organoid technologies, such as microfluidics and organ-on-chip systems, in propelling research in this field. The goal is to equip researchers with a more profound understanding of microglial ROs and their potential applications in scientific investigations.